To Serve and Protect: Examining the Relationship between Selling Alcohol in College Football Venues and Negative Fan Behaviors - Nels Popp; Archer Bane; Steven Howell; Barbara Osborne (Journal of Applied Sports Management, 2020)
Currently, many university and college athletics administrators are weighing the decision to sell alcoholic beverages at on-campus sporting events. Prior studies have found negative behaviors related to binge drinking spike on college campuses during football gamedays. However, empirical research examining the effect of a policy change regarding the selling of alcoholic beverages in college athletic venues on fan behavior remains somewhat limited. The current study examined longitudinal campus police records at 12 institutions which have recently changed their in-venue alcohol policy. Results from the analysis confirm prior studies suggesting negative behaviors increase on home football game days. The decision to sell alcohol within the campus football stadium, however, has no statistical impact on the rates of deviant behaviors recorded by campus police.
Keywords: Alcohol; Drinking; Event Management; Safety; University Athletics